Copulatory courtship, body temperature and infection in Tenebrio molitor - Cargnelutti, Franco Ignacio (2023)
Ectothermic animals can raise their body temperature under varying circumstances. Two such situations occur during sexual activity (as metabolic rate rises during copulatory movements) and during infection (to control pathogens more effectively). We have investigated these two situations using Tenebrio molitor males. We recorded the copulatory courtship behavior of sick (= infected with Metharizium robertsii fungus) vs healthy males and its link with body temperature. We predicted a positive relation between copulatory courtship (measured as antennal and leg contact behavior) and body temperature, especially in sick males. We found that the intensity of contacts correlated with increased body temperature in sick males. Previous studies in this species indicated that partner females laid fewer eggs after mating with sick males above a certain male body temperature threshold. Thus, our present findings suggest that females may detect male infection via intensity of antennal-mediated courtship, body temperature or their combination. If this is the case, females may assess male cues directly related to health status such as body temperature.